2021
DOI: 10.1515/ntrev-2021-0039
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanostructure-based superhydrophobic surfaces and coatings

Abstract: Research and development on superhydrophobic carbon nanostructures and their nanocomposites have high industrial significance. Here, a comprehensive review of the topic is provided. Reported works on superhydrophobic surfaces and coatings of carbon nanotubes, nanofibres, nanospheres/nanothorns/others, nanodiamond, fullerene and their various nanocomposites with metals, ceramics, and polymers are described. Superhydrophobic nanostructured carbon soot, graphitic carbon, and others are also presented. The section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 664 publications
0
14
0
Order By: Relevance
“…Rapid adsorption-desorption on the CNT surface resulted in active diffusion of the kerosene, which increased permeate flux [16,23,24,[30][31][32][33][34]. On the other hand, micro/nano water droplets quickly rolled and coalesced due to repulsive forces on CNTs, during which they interacted with one another and began to assemble into larger droplets [4,5,[7][8][9][10]. This enhanced water separation during the filtration process [11,12,21,25,[35][36][37][38].…”
Section: Proposed Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid adsorption-desorption on the CNT surface resulted in active diffusion of the kerosene, which increased permeate flux [16,23,24,[30][31][32][33][34]. On the other hand, micro/nano water droplets quickly rolled and coalesced due to repulsive forces on CNTs, during which they interacted with one another and began to assemble into larger droplets [4,5,[7][8][9][10]. This enhanced water separation during the filtration process [11,12,21,25,[35][36][37][38].…”
Section: Proposed Mechanismmentioning
confidence: 99%
“…There have been significant efforts in developing nanostructured membranes in various applications, and of particular interest have been carbon nanotubes (CNTs) [7,[9][10][11][12]. Recently, we have demonstrated that immobilising CNTs in different types of membranes (referred to as CNIM) alters the solute-membrane interactions [13].…”
Section: Introductionmentioning
confidence: 99%
“…11 Photothermal conversion coating is a promising material for anti/de-icing of glass surfaces. [12][13][14] Various photothermal materials, including functional inks from cuttlesh, 15 carbon-based materials, [16][17][18] metal ceramics, 19 CVD-deposited graphene, 20,21 and carbon nanotubes, 14,22,23 have been used in research studies to develop anti/de-icing surfaces. Currently, these photothermal conversion coatings are typically applied in anti/de-icing studies of aircra wings, [24][25][26] large equipment, 27,28 and under other particularly extreme environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…SEs of chemically exfoliated graphene and graphene oxide (GO) have shown to be 46.7 and 62.1 mJ/m 2 , in that order, whereas that of normal graphite flake was ∼54.8 mJ/m 2 ( Wang et al., 2009b ). As a member of carbon nanostructures and their composites, graphene has attracted extensive attention due to its high specific surface area, excellent electrical conductivity, excellent thermal conductivity, and excellent mechanical strength ( Geim, 2009 ; Saji, 2021 ). Jiang et al.…”
Section: The Practical Applicationsmentioning
confidence: 99%